PEMBELAJARAN MENULIS CERPEN MENGGUNAKAN MEDIA LAGU DAERAH SUMBAWA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS X SMAN 1 SEKONGKANG - Dian Fitri Nurullah; Rusdiawan Rusdiawan; Nuriadi Nuriadi (Center of Language and Cultural Studies, 2018)
This post-test experimental study aims to see the difference achivement of the tenth graders of SMAN 1 Sekongkang who were taught using indigeneous Sumbawa song and those who were taught using conventional materials in writing the short story. This study assigned 22 students for the experimental and 22 students for the controlled group. A test to write a short story was developed and each work was evaluated using criteria of a good short story. The results of this study show that students who received treatnents using indigeneous Sumbawa song exhibit significantly from those who received conventional media showing statistical testing at p=0.05 that is t-vale = 14.725 that is greater than t-table = 1.682.